The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/bja/aex267
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cannabinoid receptor 1 is involved in protection against mitochondrial dysfunction and cerebral ischaemic tolerance induced by isoflurane preconditioning

Abstract: Our results indicate that IPC elicits brain ischaemic tolerance and mitochondrial protection by activating the CB1R, which provides a new mechanism for IPC-induced neuroprotection against cerebral ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Consequently, administration of the chemical CypD inhibitors cyclosporine A (CsA) and gallic acid has been demonstrated to significantly diminish infarct size in vivo [85][86][87]. Additionally, isoflurane preconditioning has been reported to inhibit mPTP opening and elicit ischemic brain tolerance by activating cannabinoid receptor 1 (CB1R) [88]. The basic structure of the mPTP remains open to debate [89,90]; thus, further studies should be conducted to understand the molecular composition of the mPTP and to develop treatments targeting mPTP opening [90].…”
Section: Mitochondria and Cell Death In Ismentioning
confidence: 99%
“…Consequently, administration of the chemical CypD inhibitors cyclosporine A (CsA) and gallic acid has been demonstrated to significantly diminish infarct size in vivo [85][86][87]. Additionally, isoflurane preconditioning has been reported to inhibit mPTP opening and elicit ischemic brain tolerance by activating cannabinoid receptor 1 (CB1R) [88]. The basic structure of the mPTP remains open to debate [89,90]; thus, further studies should be conducted to understand the molecular composition of the mPTP and to develop treatments targeting mPTP opening [90].…”
Section: Mitochondria and Cell Death In Ismentioning
confidence: 99%
“…Isoflurane is a universally used inhaled anesthetic in the clinic. Some research has found isoflurane preconditioning (IP) can enhance tolerance of ischemia and play a protective role (17)(18)(19). Sun found IP supplied neuroprotection by directly regulating TLR4 expression, alleviating microglial activation, and neuroinflammation (20).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that isoflurane has a protective effect on multiple organs in the model of ischemia-reperfusion injury [911]. The neuroprotective effect of isoflurane preconditioning has also been verified several times [12, 13], but its neuroprotective mechanism remains unclear. In the middle cerebral arterial occlusion (MCAO) model, isoflurane preconditioning achieves neuroprotective effects by inhibiting the activation of microglial cells and reducing the secretion of inflammatory factors [14].…”
Section: Introductionmentioning
confidence: 99%